Preparation of Hollow Tubular TiO2/C Photocatalyst and Study on Photocatalytic Degradation Process and Mechanism of Dyes - Wang Shuhua; Tohid Islam; Zhanxia Bao (Journal of Natural Fibers, 2023)
Hollow tubular structure TiO2/C photocatalyst was prepared by carbonization at 400℃ with cotton fabric as initial carrier and tetrabutyltitanate as precursor. The structure of the samples was characterized by SEM and XRD. The results show that anatase crystal TiO2 with good crystallization is formed, TiO2 was uniformly distributed on the surface of the hollow tubular carbon material. The photocatalytic degradation performance was measured by using the methylene blue as the target dyes. When the dosage of TiO2/C was 1.7 g/L, the degradation rate of methylene blue solution was high up to 97.5%. The effective degradation of dyes was realized by using the strong adsorption property of hollow carbon materials and the high photocatalytic activity of anatase titanium dioxide. Due to the repeated adsorption of carbon materials to dyes and the continuous degradation of titanium dioxide to dyes, TiO2/C photocatalyst could be regenerated in situ.